THE RELATIONSHIP BETWEEN THE ROLE OF: HEALTH WORKERS, COMMUNITY FIGURES, FACILITATORS OF PAMSIMAS AND UTILIZATION OF HEALTHY LATRINES IN PAMSIMAS AREAS IN MENTAWAI ISLANDS DISTRICT IN 2019 - PUJI RAHAYU (Universitas Fort De Kock, 2021)
Background: The PAMSIMAS program is one of the government main program in the provision of clean water and sanitation for rural communities through a community-based approach. The problem of sanitation development in Indonesia is a socio-cultural challenge, one of the biggest problem is the behaviour of people who are accostumed to defecating in the open. This study aims: to identify the relationship between the role of: health workers, community figures, facilitators of PAMSIMAS and the utilization of healthy latrines in PAMSIMAS locations in Mentawai Islands District in 2019. Research method: quantitative research with a case control design with purposive sampling technique carried out on Januari 2020. The study population was 90 sample consist of head of familywho had accessed to healthy latrines in PAMSIMAS location in Mentawai IslandsDistrict. This researched used univariate analysis and bivariate analysis (p=0,05). Result: by using chi-square statistic, it was identified that the influential factors of the utilization of healthy latrines were health workers (p value = 0,841), the role of community figures (p value = 0,018) and the role of facilitators of Pamsimas (p value = 0,010). Conclusion: there was a significant relationship between the independent variables (the role of community figures and the role of facilitators of Pamsimas) and the dependent variable (the utilization of healthy latrines); there was no significant relationship between independent variables (the health workers) and the utilization of healthy latrines. The most influencing factor to the utilization of healthy latrine is the role of Pamsimas facilitators. Recommendation: community figures and facilitators of PAMSIMAS have to provide information about proper sanitation (healthy latrines) and their benefits to the community. It is strongly recommended to the local government to provide environmental health workers in the remote areas in Mentawai Islands Distric.